Effect of Turmeric and Garlic Inclusion to Sauropus androgynus-Bay Leaves Containing Diets on Performance, and Carcass Quality of Broilers - Urip Santoso; Yosi Fenita; Kususiyah Kususiyah; Kiki Rusdi; Elsa Marta Savitri; Novriska Winni Simanjutak (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
This study aimed to examine the effect of turmeric or garlic supplementation to fermented Sauropus androgynus-bay leaves (FSBL) containing diet on performance, carcass quality and meat organoleptic status in broilers. This study used a completely randomized design. Two hundred 15-day-old female broilers were grouped into 5 groups with 4 replications as follows: Diet with 0.5% commercial feed additive (P0); 1.25% FSBL containing diet (P1); 1.25% FSBL containing diet plus 1 g turmeric powder (P2); 1.25% FSBL containing diet plus 2 g garlic (P3); 1.25% FSBL containing diet plus 1 g turmeric and 2 g garlic (P4). The results showed that the use of turmeric or garlic to FSBL containing diet did not affect body weight gain, feed intake, feed conversion ratio, carcass weight, meat bone ratio, drip loss, and taste, odor, and texture of broiler meats (P>0.05) but affected cooking loss (P<0.05). In conclusion, the inclusion of garlic and/or turmeric to fermented Sauropus androgynus-bay leaves containing diet did not improve performance and carcass quality in broiler chickens. Any combination of medicinal plants could replace commercial feed additive.